El tratamiento contable de los intangibles: estudio exploratorio en el sector de tecnologías de la información - Pontet Ubal, Norma (2013)
In the new economy, intangible assets have become the main creators of value to many firms. However, the valuation of these assets in the accounting framework raises several issues with respect to identification, measurement and control. In this paper the valuation, measurement and recognition of intangible assets and their impact on the financial statements are presented, analyzing the asymmetry in the allocation of resources in the equity market, the growth of investments in intangible assets and the market value of the digital economy. In a group of uruguayan companies arriving at a set of initial findings for the cases. We understand the need to review and amend the rules for the treatment of intangibles, seeking to integrate more sophisticated in IT. We also understand that the rules should provide more detailed guidance on disclosure for intangible and costs-benefits for companies (from the perspective of the capital market and investors).